Manajemen Pembelajaran Aqidah Akhlak di Madrasah Ibtidayah Negeri 9 Aceh Timur - Marlinda Marlinda; Nurhayati Nurhayati; Zurriyati Zurriyati (IAIN Manado, 2023)
Management of Aqidah Akhlak Learning in Madrasah Ibtidayah Negeri 9 East Aceh. This research is entitled